2011
DOI: 10.1007/s11095-011-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene

Abstract: Gold nanoparticles, 15 nm, in aqueous solution aggregated on the skin surface. Toluene treatment eliminated skin metabolism; skin treated with toluene/gold nanoparticles (6 nm) for 24 h, but not at 4 h, showed increased nanoparticle permeability. These results are of value to nanotoxicology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 42 publications
0
68
0
1
Order By: Relevance
“…Two types of AuNPs were tested in the presence of keratinocytes for possible toxicity and to select the non or less nanocarrier toxicity [69]. As shown in Fig.…”
Section: Morphology Of Keratinocytes After Au-3mps and Au-dea Treatmentmentioning
confidence: 99%
“…Two types of AuNPs were tested in the presence of keratinocytes for possible toxicity and to select the non or less nanocarrier toxicity [69]. As shown in Fig.…”
Section: Morphology Of Keratinocytes After Au-3mps and Au-dea Treatmentmentioning
confidence: 99%
“…Localization of GNS-PEG and GNS-PEG-OAm in subcutaneous adipose tissues was further supported by TEM, which has been previously used to access the extent of nanoparticle deposition in skin layers. 40,41 TEM also revealed that the permeated nanoparticles were well dispersed inside the subcutaneous adipose tissue and eliminated the concerns of fluorescence quenching.…”
Section: In Vivo Skin Permeation Assessmentmentioning
confidence: 90%
“…[17] badali wnikanie w skórę kulistych cząstek o charakterze hydrofilowym lub hydrofobowym o średnicy 6 nm lub 15 nm, w wycinkach skóry ludzkiej od pacjentów po abdominoplastyce. Badacze wykazali większą penetrację nanocząstek o średni-cy 6 nm w porównaniu z cząstkami wielkości 15 nm.…”
Section: Przenikanie Nanocząstek Złota Przez Skóręunclassified